Monitoring Ketinggian Air dan Curah Hujan Dalam Early Warning System Bencana Banjir Berbasis IoT - Ivander Achmad Wandi; Ahmad Ashari (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2023)
Â Floods are natural disasters where there is an excessive volume of water that dampens the land. If left unchecked, flooding can bring disease, cause environmental damage and hinder people's mobility. Therefore, we need a system that can provide early warning to the community before a flood occurs. As technology develops, we can monitor the water level in an area to anticipate flooding. This concept is called the Early Warning System (EWS). IoT can help with real-time and continuous monitoring and warning of floods. IoT can also monitor air levels remotely. The MQTT protocol research also uses water level and rainfall sensors as data for flood detection. This system will detect water level and rainfall in real time. If the water level and rainfall reach a certain limit, the system will provide a warning to local residents via chatbot. There are 3 types of alerts in this system. Monitoring results are also displayed via the dashboard and sensor readings will be stored in the cloud database. The evaluation results show that the designed system can work well in providing flood early warning. Bots on Telegram have also sent notifications with an average delay of 0.561 seconds.